Lanjut Usia dengan Infark Miokard Akut yang Diduga Dicetuskan oleh Hospital-Acquired Pneumonia - Laporan Kasus: Laporan Kasus - Hardika, Putu Stephanie Apriliana; Purnami, Ni Ketut Rai (Cermin Dunia Kedokteran, 2026)
Introduction: Pneumonia can trigger acute cardiovascular events (CVE) in elderly. Risk for subsequent CVE can occur even years after pneumonia. Case: A 75-year-old male was hospitalized with chief complaint of diarrhea. During hospitalization, he complained of black stools, accompanied by cough with white phlegm, fever, and shortness of breath. As he developed into Hospital-Acquired pneumonia (HAP), he was also diagnosed as atypical angina. His electrocardiography (ECG) underwent evolution into ST elevation at lead II, III, and aVF, as well as the increasing cardiac biomarker level. The patient was diagnosed with inferior ST elevation myocardial infarction (STEMI) Killip III, intestinal amoebiasis, melena suspected caused by peptic ulcer dd/ colitis amoebiasis, moderate normochromic normocytic anemia, late onset hospital-acquired pneumonia (HAP), and acute kidney injury (AKI) stage II dd/ prerenal acute on chronic kidney disease (ACKD) caused by suspected chronic pyelonephritis dd/ nephrosclerosis. Discussion: The suspicion of pneumonia as a trigger for STEMI can be seen from the clinical manifestation of infection and the presence of significant increase in leucocytes as a marker of infection. Afterseveral days of treatment He was treated in an intensive cardiac care unit with antiplatelet and anti- angina therapy, the patient’s condition improved. Conclusion: The mechanisms underlying cardiovascular events triggered by pneumonia remain unclear. Adequate therapy playsa crucial role in the management of pneumonia.